Network safety. Problems and perspectives - Nemchenko, V. (EWDTW, 2004)
The necessity of the information protection for networks is shown. Analysis of certain types of the networks attacks is given. Principles of protection of the information in networks and perspectives are shown.This paper analysis a state of arts in the Network Safety area. The problem is actual especially taking in consideration the escalating of the network attacks amount fixed daily in the Internet. This work estimates the situation with network safety. Summary classification of attacks with the analysis of the basic attacks types is given. Some characteristics of the main types of attacks are shown. In reality today almost each server is exposed to the attack having place several times in day. The information from CERT (Computer Emergency Response Team) shows the distribution of an amount of the incidents registered in Internet coupled to a network attacks on years since 1988 (6 incidents) till today (137.529 incidents in 2003) [http://www.cert.org]. In total 319.992 cases of network attacks have been fixed during this period. The figure 1 presents this distribution.
Keywords: network safety; problems and perspectives